2009
DOI: 10.1039/b905804d
|View full text |Cite
|
Sign up to set email alerts
|

A conventional route to scalable morphology-controlled regular structures and their superhydrophobic/hydrophilic properties for biochips application

Abstract: We use a conventional and straightforward route to fabricate scalable morphology-controlled regular structures. This route is based on the etching of PDMS microlens array in CF4 and CF4/O2 plasma. PDMS microlens array can be changed to regularly isolated microdot structures array in CF4 plasma. Microbowl shaped structures array can be reached in CF4/O2 plasma. Moreover, a set of structures after CF4 plasma treatment display superhydrophobicity, while a set of structures after CF4/O2 plasma treatment present hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…The peak at 284 eV infers the occurrence of carbon. It has been previously reported that the observed peaks at the binding energy of 530 and 532 eV attributes the chemisorptions of hydroxyl groups with nickel and the adsorbed H 2 O on the surface [36][37][38][39][40]. The observed high intensity hydroxyl peaks indicate the inclusion of a large amount of surface oxygen absorbed by the material.…”
Section: Resultsmentioning
confidence: 78%
“…The peak at 284 eV infers the occurrence of carbon. It has been previously reported that the observed peaks at the binding energy of 530 and 532 eV attributes the chemisorptions of hydroxyl groups with nickel and the adsorbed H 2 O on the surface [36][37][38][39][40]. The observed high intensity hydroxyl peaks indicate the inclusion of a large amount of surface oxygen absorbed by the material.…”
Section: Resultsmentioning
confidence: 78%
“…This lack of a need for superhydrophobic confinement reduces the processing steps. Ren et al nanotextured PDMS with preformed microlens structures in CF 4 and CF 4 /O 2 plasmas and noticed that while the first plasma produced superhydrophobic surfaces, the second plasma produced hydrophilic nanotextured areas on which DNA could be enriched [162] (see Fig. 8(ii)).…”
Section: Biomolecule and Other Molecule Adsorption Control Fouling Amentioning
confidence: 95%
“…Superhydrophobic surface is the earliest and the most widely studied interface in the field of superwettability because of its remarkable water repellence . Inspired by the superhydrophobicity of lotus leaf, thousands of artificial superhydrophobic surfaces have been fabricated, and those surfaces are wildly applied in self‐cleaning coatings, microdroplets manipulation, oil/water separation, anticorrosion, antifog/ice/snow, drag reduction, antifouling, cell engineering, water collection, microfluidics, lab chips, etc. After more than 20 years of development, both the basic theory and the fabrication technologies for superhydrophobic surfaces have reached a high level.…”
Section: Introductionmentioning
confidence: 99%